Alteraciones oculares por miopía magna que causan baja visión (2020)
Currently, myopia magna has increased significantly, in 2010 figures of 170 million people were presented worldwide and 925 million people are projected by the year 2050 (1), this disease has conditions at the eye level and can be causing low vision. Objective: to determine the ocular pathologies associated with great myopia that produce low vision. Methodology: review of narrative literature in databases such as Scielo, pubMed, Elservier, between the years 2000 to 2020. Results: ocular findings of magna myopia were found that can generate low vision such as posterior staphyloma, retinoschisis, foveoschisis, chorioretinal atrophy, among others, these alterations generate damage to layers of the retina, choroid, macula and fovea that can lead to mainly rhematogenous retinal detachment. Conclusions: low vision due to great myopia is mainly due to alterations such as posterior staphyloma, choroidal neovascularization, and retinal detachment, since they progressively decrease visual acuity and visual field.